2013
DOI: 10.1093/cercor/bht083
|View full text |Cite
|
Sign up to set email alerts
|

The Pathways for Intelligible Speech: Multivariate and Univariate Perspectives

Abstract: An anterior pathway, concerned with extracting meaning from sound, has been identified in nonhuman primates. An analogous pathway has been suggested in humans, but controversy exists concerning the degree of lateralization and the precise location where responses to intelligible speech emerge. We have demonstrated that the left anterior superior temporal sulcus (STS) responds preferentially to intelligible speech (Scott SK, Blank CC, Rosen S, Wise RJS. 2000. Identification of a pathway for intelligible speech … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
82
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 43 publications
9
82
2
Order By: Relevance
“…Using this metric, they argued that posterior STS showed the greatest invariance to the acoustic properties of the stimuli. In another fMRI replication of this paradigm, Evans, Kyong et al (2014) used both univariate and multivariate analyses, showing the strongest univariate intelligibility response in left anterior STS but the greatest multivariate classification accuracy in local patches of cortex (searchlights) in the posterior STS. Yet, when exploring classifications in which information could be integrated across the whole temporal lobe, they found that the most informative voxels showing preferential responses to intelligible speech were located in anterior regions.…”
Section: (A) Understanding the Temporal Hierarchy: Anterior Versus Pomentioning
confidence: 99%
See 1 more Smart Citation
“…Using this metric, they argued that posterior STS showed the greatest invariance to the acoustic properties of the stimuli. In another fMRI replication of this paradigm, Evans, Kyong et al (2014) used both univariate and multivariate analyses, showing the strongest univariate intelligibility response in left anterior STS but the greatest multivariate classification accuracy in local patches of cortex (searchlights) in the posterior STS. Yet, when exploring classifications in which information could be integrated across the whole temporal lobe, they found that the most informative voxels showing preferential responses to intelligible speech were located in anterior regions.…”
Section: (A) Understanding the Temporal Hierarchy: Anterior Versus Pomentioning
confidence: 99%
“…By now, a number of studies have used pattern classification as a metric for quantifying the relative contribution of different regions to acoustic and linguistic processes in the case of connected speech signals (Abrams et al, 2012;Evans, Kyong et al, 2014;McGettigan, Evans et al, 2012;Okada et al, 2010). Correia et al (2014) extended this approach using an innovative cross decoding approach (see Kaplan, Man, & Greening, 2015 for a review of cross decoding) to demonstrate the encoding of abstract word representations independent of speech acoustics.…”
Section: (A) Understanding the Temporal Hierarchy: Anterior Versus Pomentioning
confidence: 99%
“…Although traditional universal grammar theory argues that functional components of linguistic ability are manifest without being taught (10), recent connectionist theory within a neural network approach emphasizes interactions among primary systems of neuronal processing units that support language acquisition and use, where the weights of connections among these units are gradually changed during learning and thus highly constrained by the unique feature of a given language (9,11,12). Related with connectionist views, the dual pathway model of language based on evidence from neuroimaging and anatomical studies was also framed to interpret the neural basis of language comprehension and production (13, 14), especially in speech comprehension.Intelligible speech is processed hierarchically in human neocortex, with the anterior temporal (13,15,16) and frontal cortices (Broca's area) operating at a higher hierarchical level than the posterior region centered on superior temporal sulcus/gyrus (pSTS/pSTG, core of Wernicke's area), which itself receives inputs from primary and secondary auditory cortices (17). In the dual ventral-dorsal pathway model, the dorsal-stream pathway of speech processing assumes primary processing begins in the Significance Language processing is generally left hemisphere dominant.…”
mentioning
confidence: 99%
“…Intelligible speech is processed hierarchically in human neocortex, with the anterior temporal (13,15,16) and frontal cortices (Broca's area) operating at a higher hierarchical level than the posterior region centered on superior temporal sulcus/gyrus (pSTS/pSTG, core of Wernicke's area), which itself receives inputs from primary and secondary auditory cortices (17). In the dual ventral-dorsal pathway model, the dorsal-stream pathway of speech processing assumes primary processing begins in the Significance Language processing is generally left hemisphere dominant.…”
mentioning
confidence: 99%
“…Becker, Pefkou, Michel, & Hervais-Adelman, 2013;Ding, Chatterjee, & Simon, 2014;Obleser & Weisz, 2012;Peelle, Gross, & Davis, 2013) and imaging work (e.g. Davis & Johnsrude, 2003;Evans et al, 2014;Scott, Blank, Rosen, & Wise, 2000).…”
Section: Introductionmentioning
confidence: 99%